2017
DOI: 10.3390/pharmaceutics9020013
|View full text |Cite
|
Sign up to set email alerts
|

Blend Hydrogel Microspheres of Carboxymethyl Chitosan and Gelatin for the Controlled Release of 5-Fluorouracil

Abstract: Carboxymethyl chitosan (CMCS) was synthesized and blended with gelatin (GE) to prepare hydrogel microspheres by w/o emulsion cross-linking in the presence of glutaraldehyde (GA), which acted as a cross-linker. 5-Fluorouracil (5-FU) was encapsulated to investigate its controlled release (CR) characteristics in acidic (pH 1.2) and alkaline (pH 7.4) buffer media. The microspheres which formed were spherical in nature, with smooth surfaces, as judged by the scanning electron microscopy (SEM). Fourier transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…XRD patterns of pure 5FU, and PU and PU 5FU coatings were recorded ( Figure 3 ) and d -spacing values were determined for prominent peaks ( SI, Table S4 ). Pure 5FU revealed a series of characteristic diffraction peaks consistent with those reported previously [ 42 , 56 , 59 , 61 , 69 , 70 ], with a prominent 2 θ peak at 28.6° corresponding to a d -spacing of 3.123 Å. The diffractogram of the PU coating revealed a broad 2 θ peak at 19.9° and a low intensity 2 θ peak at 29.2°, which are consistent with previous literature reports and can be attributed to amorphous and semicrystalline segmented polycarbonate-PUs [ 43 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…XRD patterns of pure 5FU, and PU and PU 5FU coatings were recorded ( Figure 3 ) and d -spacing values were determined for prominent peaks ( SI, Table S4 ). Pure 5FU revealed a series of characteristic diffraction peaks consistent with those reported previously [ 42 , 56 , 59 , 61 , 69 , 70 ], with a prominent 2 θ peak at 28.6° corresponding to a d -spacing of 3.123 Å. The diffractogram of the PU coating revealed a broad 2 θ peak at 19.9° and a low intensity 2 θ peak at 29.2°, which are consistent with previous literature reports and can be attributed to amorphous and semicrystalline segmented polycarbonate-PUs [ 43 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 88%
“…DSC was used to investigate the presence of 5FU crystallites within the PU matrix and possible changes in the thermal properties of the PU after drug incorporation. The thermogram of pure 5FU revealed a sharp endothermic peak at 282 °C corresponding to its melting ( Tm ) and degradation temperatures ( Td ) ( Figure 6 ) [ 32 , 59 , 61 ], whereas the thermogram of PU film displayed a glass transition temperature ( Tg ) of ~106 °C, which is consistent with interactions between hard urethane segments [ 62 , 76 ]. In comparison, the thermogram of PU 5FU films revealed a small, sharp endothermic peak at 285 °C consistent with the 5FU Tm and a Tg at ~99 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blended microspheres were examined with different analytical techniques to understand the interaction of the polymer and 5-FU. As a result, the in vitro release of 5-FU increased to 12 h at a physiological pH, 82 with an expected enhancement for nanospheres.…”
Section: Applications Of Chitosan (Cs) and Its Blend Derivatives In Cddssmentioning
confidence: 83%
“…The controlled release of a drug may lower its side effects and increases its therapeutic effect on tumors. The complexation of 5‐FU or its derivatives (for example tegafur) inside βCD attached to polymeric vectors, carbon materials, or iron oxide nanoparticles, were reported. The in vitro or in vivo studies revealed the therapeutic potential of the designed 5‐FU delivery platforms.…”
Section: Introductionmentioning
confidence: 99%